(untitled) (Journal of Applied Oral Science, 2004)
Over the last decade, the classic concept of 3-step bonding to dental tissues has developed rapidly to more user-friendly, simplified adhesive systems. These comprise the total-etch 2 step, self-etch 2step and the self-etch "all-in-one" adhesives. These adhesives carry along with simplicity some characteristics that are relevant to their efficacy in providing long-lasting bond stability. They share with the glass ionomer cements a class of materials that have high affinity for water. Such hydrophilicity renders such adhesives very permeable and denies their ability to hermetically seal dentin surfaces. Additionally, the water flux across simplified adhesives may compromise bonding in certain circumstances and their durability in the oral environment. This paper presents evidences of the water transport across simplified adhesive systems and glass ionomer cements and relates them with clinical implications of the phenomenon.